TOWARDS A NATIONAL POLICY FOR THE APPLICATION OF COMPUTER TECHNOLOGY IN DEVELOPING COUNTRIES - EL-MILIGI, DR. IBRAHIM S. (Dirasat in Economics and Business, 1979)
Developing countries are faced with the difficult task of mobilizing their resources to enhance economic and social de velopment. The resources are usually scarce and tightly stretch ed although a few countries are endowed with sufficient natural resources to form a basis for a rapid economic and social development.